Reduction product morphology of the spherical molybdenum trioxide - YANG Qin-li; ZHUANG Fei; XI Sha; BU Chun-yang; CUI Yu-qing; HE Kai (Fenmo yejin jishu)
The morphology of MoO2 and Mo powders prepared by the two-stage hydrogen reduction experiment of the spherical molybdenum trioxide powders was studied. The results show that, the spherical molybdenum trioxide (β-MoO3) is transformed into α-MoO3 firstly, and then the square γ-Mo4O11 is regenerated to form α-MoO2 in first stage hydrogen reduction; Molybdenum powders are obtained in second stage hydrogen reduction. The morphology of MoO2 is greatly affected by the reduction temperature and reduction atmosphere, the MoO2 powders with fine and loose irregular morphology are obtained at low reduction temperature or by importing the water vapor into the reduction atmosphere; the MoO2 powders with flake and hardened are formed at the higher reduction temperature or in the dry hydrogen with large flow. The morphology of ultrafine Mo powders is mainly affected by the reduction temperature, the water vapor partial pressure, and the hydrogen partial pressure. When the reduction temperature is low or the hydrogen flow rate is small, the ratio of the water vapor partial pressure and the hydrogen partial pressure should be close to the equilibrium constant as far as possible, and the uniform and dispersed ultra-fine molybdenum powders can be obtained.